The role of HLA-B27 molecules in the pathogenesis of ankylosing spondylitis - A. Cauli; G. Dessole; P.P. Nurchis; A. Vacca; A. Mameli; P. Garau; R. Pala; G. Passiu; A. Mathieu (PAGEPress Publications, 2002)
Ankylosing Spondylitis (AS) is characterised by the strongest association with an HLA antigen ever described for any disease. It represents therefore the ideal model for the understanding of the link between immune-mediated diseases and the HLA system. The role of HLA-B27 in the pathogenesis of AS will be discussed focusing on the recently described higher expression of these molecules in patients with AS compared with healthy controls.